Preparation of Polyacrylonitrile-Polyethersulfone Nanofibers Loaded with Reduced Graphene Oxide from Palm Kernel Shell forWastewater Filtration - Dani, Rahma; Almafie, Muhammad Rama; Mataram, Agung; Lamura, M. Danny Pratama; Akhsan, Hamdi; Marlina, Leni; Fudholi, Ahmad; Ismail, Ahmad Fauzi; Sriyanti, Ida (Science and Technology Indonesia, 2026)
The development of Polyacrylonitrile (PAN)–Polyethersulfone (PES) nanofiber membranes loaded with Reduced Graphene Oxide (rGO) offers an innovative and sustainable solution for water filtration. This study synthesized and characterized PAN–PES loaded rGO nanofiber membranes using an electrospinning technique. A PAN–PES mixture (8:2 mass ratio) at 10–20 wt% served as the matrix, with 48 mg of rGO added. The membranes were analyzed using scanning electron microscopy, Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), mechanical testing, water absorption, immersion resistance, and clean water permeability (CWP). The resulting nanofibers exhibited defect-free, bead-free, and uniform morphology with diameters ranging from 389 to 757 nm. FTIR confirmed hydrogen bonding between PAN–PES and rGO, while XRD showed sharp peaks with a maximum crystallinity of 33.52%. The membrane displayed a Young’s modulus of 57.83 MPa and remained stable after 32 days of immersion. It demonstrated superhydrophilic behavior with a contact angle of 72.4o to 74.3o, sustaining a stable water flux at 6.0 bar for 60 min, yielding a permeability of 3.25 to 23 L/m2.h.bar and an equilibrium water content of 69 to 91%. Surface morphology before and after wastewater filtration revealed effective contaminant capture and strong antifouling resistance. These results confirm that PAN–PES loaded rGO nanofiber membranes possess excellent mechanical stability, high permeability, and superior wettability, providing a promising pathway for advanced, sustainable water filtration applications.